Diseminasi Media Pembelajaran Berbasis Flippbook untuk Mendukung Asyncrhonous Learning di SMP-SMA Bunda Kandung Jakarta - Ageng Triyono; Nurimani Nurimani; Rusdi Hamdany Nuary; Teguh Wibowo (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The purpose of this community service is to develop teaching materials to meet the learning needs of asynchronous learning. The teaching materials developed are in the form of electronic modules and electronic worksheets based on flipbooks. The service method carried out is in the form of a dissemination program whose stages are carried out in a hybrid manner. The service stages consist of the stage of developing teaching materials which are carried out offline and is followed by the stage of socializing and monitoring which is carried out online. The target of this service is the mathematics teacher at Bunda Kandung Middle and High School, Jakarta. The activity evaluation instrument is in the form of a questionnaire. The results of the questionnaire showed that the teacher as the party receiving the benefits stated that he was satisfied with the media developed and the media could be used as an alternative solution to the current needs of teaching materials. The results of the monitoring phase indicated that the teaching materials developed have begun to be implemented and have succeeded in meeting the needs of teaching materials needed by schools. So, it can be concluded that this activity has succeeded in achieving the expected goals.